2020
DOI: 10.1186/s12885-020-07177-6
|View full text |Cite
|
Sign up to set email alerts
|

High BANCR expression is associated with worse prognosis in human malignant carcinomas: an updated systematic review and meta-analysis

Abstract: Background BRAF-activated noncoding RNA (BANCR) is aberrantly expressed in various tumor tissues and has been confirmed to function as a tumor suppressor or oncogene in many types of cancers. Considering the conflicting results and insufficient sampling, a meta-analysis was performed to explore the prognostic value of BANCR in various carcinomas. Methods A comprehensive literature search of PubMed, Web of Science, EMBASE, Cochrane Library and the China National Knowledge Infrastructure (CNKI) was conducted t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In addition, Zhou and Gao (2016) described a key role for up-regulated BANCR in the occurrence and development of hepatocellular carcinoma and the prognosis of affected patients, proposing its application as an lncRNA biomarker for early diagnosis of cancer and prognosis screening. A recently published meta-analysis reported the association of an undesirable prognosis for most cancer patients with elevated BANCR expression (Fang et al, 2020). Sun et al (2016b) showed higher ANRIL expression in CRC tissue compared with adjacent non-tumour tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhou and Gao (2016) described a key role for up-regulated BANCR in the occurrence and development of hepatocellular carcinoma and the prognosis of affected patients, proposing its application as an lncRNA biomarker for early diagnosis of cancer and prognosis screening. A recently published meta-analysis reported the association of an undesirable prognosis for most cancer patients with elevated BANCR expression (Fang et al, 2020). Sun et al (2016b) showed higher ANRIL expression in CRC tissue compared with adjacent non-tumour tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on BANCR and CRNDE function on tumor procession have shown conflicting results. For BANCR, some researchers have identified its influence in tumor invasion and migration ( 26 ). In contrast, overexpression of BANCR can control the content of N-cadherin, and vimentin and E-cadherin were shown to inhibit EMT in another study.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent evidence has demonstrated that the dysregulation of BANCR contributes to the progression of some cancers, including colorectal cancer, 24 papillary thyroid carcinoma, 25 bladder cancer, 26 T h i s c o n t e n t i s breast cancer, 22,27 endometrial cancer, 23 and hepatocellular carcinoma, 28 and increased BANCR expression causes poor prognosis and a shorter survival rate of cancer patients. 29 BANCR promotes cell proliferation of gastric cancer via the regulation of NF-kappaB1, 30 and lower expression of BANCR was related to the initiation and progression of non-small-cell lung cancer. 31 In eosinophilic esophagitis, BANCR is dysregulated and can be induced by IL-13 through the regulation of innate immune genes.…”
Section: ■ Introductionmentioning
confidence: 94%
“…BANCR was first described as a cancer-promoting lncRNA in melanoma tissues in 2012, with a length of 693 bp and location on chromosome 9. Subsequent evidence has demonstrated that the dysregulation of BANCR contributes to the progression of some cancers, including colorectal cancer, papillary thyroid carcinoma, bladder cancer, breast cancer, , endometrial cancer, and hepatocellular carcinoma, and increased BANCR expression causes poor prognosis and a shorter survival rate of cancer patients . BANCR promotes cell proliferation of gastric cancer via the regulation of NF-kappaB1, and lower expression of BANCR was related to the initiation and progression of non-small-cell lung cancer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation